2023
DOI: 10.1186/s12877-023-03743-2
|View full text |Cite
|
Sign up to set email alerts
|

A combination of Beers and STOPP criteria better detects potentially inappropriate medications use among older hospitalized patients with chronic diseases and polypharmacy: a multicenter cross-sectional study

Abstract: Background Research on potentially inappropriate medications (PIM) and medication-related problems (MRP) among the Chinese population with chronic diseases and polypharmacy is insufficient. Objectives This study aimed to investigate the prevalence of PIM and MRP among older Chinese hospitalized patients with chronic diseases and polypharmacy and analyze the associated factors. Methods A retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…A higher prevalence rate has also been observed in other studies. A study conducted in China reported 93.8% of PIM prevalence 25 and a Portuguese study reported the prevalence of PIMs to be 92%. 26 However, a study conducted in Riyadh, Saudi Arabia, reported that the prevalence of PIM in older adults was 57.2%, 63.6% and 60.4% in 2017, 2018 and 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence rate has also been observed in other studies. A study conducted in China reported 93.8% of PIM prevalence 25 and a Portuguese study reported the prevalence of PIMs to be 92%. 26 However, a study conducted in Riyadh, Saudi Arabia, reported that the prevalence of PIM in older adults was 57.2%, 63.6% and 60.4% in 2017, 2018 and 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers of this study stated that one of the main causes is high polypharmacy ( ≥ 10 drugs) in older adults. 16 The difference in the type of used drugs can be one of the reasons for obtaining different results in different countries. Further, there may be several inappropriate drugs according to the Beers criteria in the essential drug list of some countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperpolypharmacy (taking ≥10 medications) and the presence of coronary heart disease were the main factors of PIM [ 40 ]. Studies from Europe and North America indicate that PIMs and subsequent adverse drug reactions may cause 1.5-15% of emergency department visits and unplanned hospitalizations among older people [ 41 ]. In two cross-sectional retrospective studies conducted in the central region of Saudi Arabia, almost one out of two older adult patients (age ≥ 65 years) treated in an ambulatory care setting had used PIMs.…”
Section: Reviewmentioning
confidence: 99%